Dinamika pohon mahoni (Swietenia macrophylla King) pada agroforestry pola lorong (alley cropping) = Mahoni (Swietenia macrophylla King) trees dynamics in Alley cropping agroforestry - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Along with time, the growth of Swietenia macrophylla King tree component under alley cropping, will limit the farmers chance to grow their crops. However, under given condition, there is arising question about the time duration i.e. how long could the system work before any crown treatments have to be practiced. This question leading to the observation of crown of mahoni trees of various aged available in the existing alley cropping system to formulate a crown development model. This research was carried out by measuring sample trees of different ages randomly taken from each of 10-m tree-row experimental units of mahoni-based alleycropping stands, making a total number of 100 sample trees Results showed that up to 10 years of age the alley cropping has : In-row tree distance of 1.1761 ± 0.1152 metre